The impact of dispersal powers on congregating youth. Issue 4 (10th October 2016) - Cockcroft, Tom; Bryant, Robin; Keval, Harshad
Abstract : Purpose: The purpose of this paper is to present research which evaluated the impact of Dispersal Orders in an English town. Design/methodology/approach: The study used a mixed method design to, qualitatively, explore the impact of the intervention on young people and, quantitatively, the impact on recorded crime/anti-social behaviour. Findings: The use of Dispersal Orders in the town being studied highlighted a number of issues detrimental to young people. Powers appeared to be used to control the congregating rather than anti-social behaviour of young people and their use could increase young peoples' feelings of vulnerability. Practical implications: The findings suggest that Dispersal Orders (and the newer Public Spaces Protection Orders (PSPOs)) may be ineffective if they are used without the focus of a specific anti-social behaviour issue. Social implications: The findings suggest that the use of Dispersal Orders to deal with non-anti-social behaviour issues are likely to alienate young people and have the potential to inadvertently place them at further risk. They also suggest that the PSPO could very well exacerbate the substantial issues which have been identified in the present research. Originality/value: This research is original and suggests that the negative findings of earlier pieces of research into Dispersal Orders can be replicated in very different geographical environments and in areas with low levels of general deprivation where no substantial anti-social behaviour issues were identified. Furthermore, it uses original data to contextualize contemporary developments in anti-social behaviour, namely the introduction of PSPOs.